Fabrication of micro-scale features on titanium alloys through micromilling. - Dickins, Andrew (Cranfield University, 2018)
Structured surfaces are of high interest in the manufacturing world, allowing for functionality to be applied to materials through nothing more than a change in the surface topography or an application of a surface coating. Applications for these surfaces range greatly, including, optical surfaces for antireflective surfaces, thermal structures to assist in heat dispersion and anti-fouling surfaces to reduce organisms from adhering to components. Hydrophobic structures, such as the one that have been examined on the lotus leaf under SEM, generate high droplet contact angles and roll off. The manipulation of surface wettability is of particular interest in areas such as the medical sector for self-cleaning applications or controlling cell adhesion on the surface of an implant. This work investigates the generation of micron level hydrophobic features on two Titanium alloys, Ti-6Al-4V alpha-beta alloy and Ti-30Nb beta alloy, with the aim of identifying how accurately surface structures can be produced through micromilling as well as experimentally testing how successfully these surfaces function after being fabricated. On each alloy, nine different 5mm x 5mm test pillars are machined using micromilling, half of each pillar is machined with 200μm wide and 30μm deep channels, generating a hydrophobic groove structure, and the other half being flat machined. Across these nine pillars the feedrate, spindle speed, axial depth of cut and tool step over were varied to optimise these parameters in terms of structure generation, channel bottom surface roughness and tool to workpiece interaction in an attempt to determine how effective micromilling is as at structuring the surface of beta Titanium alloys. Tool condition was assessed qualitatively using SEM imaging and an independent assessment was carried out to determine the mechanical properties of the beta Titanium alloy being machined.
Keywords: Beta Ti; biomedical; hydrophobicity; end milling; fabrication; structure generation